Securitization and Militarization of The Border: Security Dilemma in Post-1998 Ethiopia and Eritrea - Gebrewahd, Meressa Tsehaye (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
The post-1991 Ethiopia and Eritrea were hoped to become promising and exemplary states in Africa. But, after seven years of euphoria, national stability and security trapped both countries into a bloody conflict, and their relation is now in structural crisis: the ‘no war, no peace’ dilemma. Their security dilemmas are basically centered on the antagonistic foreign and national security as well as nation-building policies. The post-independence nation-building attempt to forge a militarized single national identity in Eritrea, under the motto of “one people, one heart” and the remaking of the age-old Ethiopian state based on ethnic federalism further deepen the nation-building dilemma. The post-1998 security dilemma between the two states is, therefore, the result of securing Eritrea’s nation-building policies and the militarization of the Yika’alo-Warsay generation where Ethiopia has been made to be “a relevant enemy to its Singaporization vision” and Eritrea is subsequently viewed as a “relevant enemy to Ethiopia’s renaissance vision and securitization of poverty”. During the militarization of the borders, Badme still remains symbolically the hotbed of the ‘no war, no peace’ regime. This article, therefore, analyzes the post-2000 security dilemma between Ethiopia and Eritrea and the subsequent dynamics that have led to securing and/or militarizing their relations.